Synthesis and Characterization of Bulk Al-Cu-Fe Based Quasicrystals and Composites by Spray Forming - Mukhopadhyay N.K.; Uhlenwinkel V.; Srivastava V.C. (My University, 2025)
The bulk quasicrystalline (QC) materials and their composites have attracted considerable interest due to their promising mechanical properties. In the present investigation, spray forming has been used to synthesize bulk single-phase icosahedral quasicrystals and composites in Al62.5Cu25Fe12.5 system as well as in quaternary system containing 10% Sn. The elemental materials were induction melted under nitrogen cover and a billet of 250 mm in diameter and 350 mm in height was spray formed. The phase constitution of the spray-formed materials showed a bulk single-phase icosahedral quasicrystal as a major phase along with other crystalline phases. A large number of annealing twins were observed in the microstructure in ternary AlCuFe alloys. It is interesting to note that due to addition of Sn, the volume fraction of β-Al(CuFe) phase was found to increase and annealing twins were almost absent. The hardness of the single-phase AlCuFe alloy and Sn-containing composites was found to be 8.6 and 6.0 GPa, respectively, at a load of 300 g. In general, the hardness decreases with heat treatment at high temperatures. However, in case of Sn-containing alloy, hardness increases with low-temperature heat treatment. Long and hair-like cracks (Palmqvist type) are observed to form from the corner of the indentations of the ternary alloys, whereas in Sn-containing composites, the cracks are not sharp and long suggesting the enhancement of fracture toughness in the composites. Attempts have been made to understand the effect of Sn on the evolution of icosahedral phase, other crystalline phases and their composite effects on the mechanical properties. © 2015, ASM International.